Sistem Irigasi Otomatis pada Tanaman Padi Menggunakan Arduino dan Sensor Kelembapan Tanah - Rianto Setiobudio; Cosmas Eko Suharyanto (Jurnal ICT : Information Communication & Technology, 2019)
Not all regions of Indonesia can feel rice harvest up to 3 times in 1 year. This is because for the last few years rainfall is uncertain. This causes a lack of water for rice irrigation. Arranging water irrigation based on soil moisture and arduino then the water that existed during the dry season is expected to meet the need for irrigation or rice. Water dispersion using soil moisture sensor applied on rice with compost planting medium in bucket container with diameter 42 cm and compost depth 18 cm then got 18.6 liter water usage in 3,8 mounth or 115 days, in the same time while waterlogging on rice uses 20,3 liters of water. the soil moisture sensor will read the lower bound of the soil moisture that is 80% of the saturation of the soil at a value of 626. If the value is read below from that value then the arduino will turn on the relay and the pump will drain the water to the rice plant, as well as vice versa.